A partial similitude method for vibration responses of rotor systems: Numerical and experimental verification. (15th October 2021) - Li, Lei; Luo, Zhong; He, Fengxia; Ding, Zhe; Sun, Kai
Highlights: This paper proposes a method to obtain scaling laws for rotor systems. This paper proposes frequency adjustment laws for predicting responses in non-resonant state. The proposed method provides several scaling laws in whole range of rotating speed. Experimental testing for vibration responses of prototype and model is carried out. The proposed method can improve prediction accuracy compared with existing methods. Abstract: Similitude theory provides the necessary conditions to predict the structural responses of the full-scale prototype through the scaled model, and is widely used in full-scale experiments of large structures. However, the prediction accuracy is insufficient in partial similitude. Aiming at this issue, this paper proposes the frequency adjustment laws to predict vibration responses of full-scale rotor in non-resonant state, since the rotating machinery usually works in non-resonant state. On this basis, a partial similitude method is presented by combining the frequency adjustment laws with the current method. The proposed method provides several scaling laws in the whole range of rotating speed, while only one scaling factor is used to predict the vibration responses in existing methods. The accuracy of the proposed method is verified by the numerical and experimental case studies, where the geometrical distortion is considered. In the numerical case study, the scaling laws of a rotor system are obtained by the proposed method and existing methods. The predicted results of the proposed method are compared with those of the existing methods. It is found the proposed method accurately predicts the displacements and accelerations of prototypes through those of scaled model. Moreover, the proposed method achieves a higher accuracy. The experimental study carries out the testing for the prototype and model test rigs. The experimental results show that the proposed method provides better results in predicting the displacement and acceleration compared with the existing methods. The proposed method allows designers to design a scaled model and to reproduce the vibratory behavior of the full-size prototype, which reduces the difficulty, costs and time of experimental test. Moreover, the proposed partial similitude method has a better performance than the existing methods. Graphical abstract: Image, graphical abstract